2016
DOI: 10.1590/s1984-82502016000400003
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a HPTLC method for analysis of Sunitinib malate

Abstract: A simple high performance thin layer chromatography (HPTLC) has been developed and validated for determination of sunitinib malate and possible impurities. The samples were applied in forms of bands on an aluminum TLC plate pre-coated with silica gel and were separated using dichloromethane: methanol: toluene: ammonia solution as the mobile phase. Sunitinib malate was thoroughly separated from impurities including E-isomer, sunitinib N-oxide and impurity B with a retention factor (RF) of 0.35±0.02. Quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The abovementioned score for both HPLC techniques showed a lower AGREE score, suggesting that the reported methods are not greener compared with present HPTLC methods for the analysis of lenvatinib in both bulk and capsule formulation. As the HPTLC method was not reported for the estimation of lenvatinib, we have compared our developed methods with HPTLC methods developed for other similar drugs, namely, sorafenib tosylate and sunitinib malate. , For the stated HPTLC technique for sorafenib tosylate and sunitinib malate, Figure E,F exhibited AGREE tool scores of 0.62 and 0.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abovementioned score for both HPLC techniques showed a lower AGREE score, suggesting that the reported methods are not greener compared with present HPTLC methods for the analysis of lenvatinib in both bulk and capsule formulation. As the HPTLC method was not reported for the estimation of lenvatinib, we have compared our developed methods with HPTLC methods developed for other similar drugs, namely, sorafenib tosylate and sunitinib malate. , For the stated HPTLC technique for sorafenib tosylate and sunitinib malate, Figure E,F exhibited AGREE tool scores of 0.62 and 0.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the other four reported techniques (methods 3 to 6) were quantitatively analyzed for the use of reagents, and it was observed that very few renewable reagents were used for the analysis, and many of the reagents were not from renewable sources. The toxic solvents (dichloromethane, toluene, ammonia solution, and n -hexane) and toxic substances (ammonium acetate and ammonium bicarbonate) , were used in large volumes which were very harmful to the environment, operator, and aquatic life. Hence, a score of 0.5 is given for methods (3 to 6) by the AGREE tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quality control (QC) of TKIs, it is absolutely necessary to use proper analytical techniques. The analytical methods mentioned in the literature for QC of TKIs in their dosage forms are HPLC and HPTLC [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], voltammetry [ 28 ], spectrofluorometry [ 29 , 30 , 31 , 32 ] and spectrophotometry [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The most accessible methodology is spectrophotometry, which is quite easy, the least expensive and available in most quality control laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…HPTLC is an advanced form of instrumental TLC and it is generally used with an unmodified silica layer as stationary phase on precoated plates and slit-scanning densitometry with UV-vis light as the detection technique 13 . HPTLC has simplicity of procedure, efficiency with small amounts of sample, parallel analysis of samples, multiple nondestructive methods for detection, numerous options for developing solvents, low consumption of solvents, time and cost effectiveness (In fact, the expenses associated with providing solvents and maintenance are much lower in comparison with HPLC) 5 . These advantages enable this method to be an important alternative to other chromatographic techniques such as HPLC for determining thiamine in green beans.…”
Section: Introductionmentioning
confidence: 99%